A NEW GALACTIC CLUSTER IN AURIGA - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1961)
A faint galactic cluster has been discovered at 5h 47.3m and +33° 37'1. The data were obtained on plates, taken with the Tonantzintla Schmidt camera. Assuming that this galactic cluster belongs to Trumplers's class IIIm, its distance cannot be less than 4
BOL OBS TONAN TACUB
Keywords: NEW, GALACTIC, CLUSTER, AURIGA; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS